MODERN LIBRARY MANAGEMENT SYSTEM: A WEB-BASED FRAMEWORK FOR RESOURCE AUTOMATION AND USER OVERSIGHT - Bhati, Pawan; Komal; Prince; Saxena, Stuti (International Journal of Research -GRANTHAALAYAH, 2024)
This project presents the design and development of an advanced Library Management System (LMS) aimed at optimizing daily operations such as book transactions, member registration, inventory control, and administrative oversight. The proposed system replaces traditional manual processes with a streamlined, automated framework that enhances data accuracy, operational efficiency, and user experience. Developed primarily for librarians and library administrators, the system facilitates seamless management of key modules including book maintenance, member records, issue/return tracking, and lost book handling. Additionally, administrative users are granted access to staff management and comprehensive reporting functionalities for operational analytics. The LMS is designed as a web-based platform, offering centralized control over library resources and enabling real-time updates to book status and user interactions. The system significantly reduces the overhead associated with manual operations, minimizes human errors, and improves resource utilization by incorporating automated validation and modular design. Unlike conventional library systems, this model identifies and addresses limitations such as the absence of One-Time Password (OTP) authentication, lack of automated due-date reminders, and the non-integration of smart card access. To ensure future readiness, the system architecture allows scalability for advanced features such as OTP-based user verification, SMS/email reminders for overdue books, and smart card-based user identification. By integrating these emerging technologies, the proposed LMS establishes a robust foundation for intelligent, secure, and user-centric library management in academic and institutional environments.